37 Use of prolyl hydroxylase inhibitors to induce HIF-related metabolic changes and increase c-Kit expression in cardiosphere-derived cells. Issue 20 (23rd September 2011) - Tan, S C; Yeoh, K K; Carr, C A; Heather, L C; Ambrose, L; Tan, J J; Schofield, C; Clarke, K
Abstract : Cardiosphere-derived cells (CDCs) can improve function in infarcted hearts, but the potential of CDC therapy is limited due to the low retention rate and the time required to obtain sufficient cells for transplantation. Hypoxic preconditioning increases CDC proliferation and expression of the cardiac stem cell marker, c-Kit. AIM: Here, we aim to establish hypoxic conditions using the prolyl hydroxylase inhibitors (PHIs): DMOG, KKC226 and FG-2216 in order to enhance CDC potential for myocardial infarction therapy. Methods: Rat heart explants were cultured on fibronectin to generate explant-derived cells (EDC), which were isolated and cultured to form cardiospheres (Csp). Csp were expanded into monolayer CDCs and treated with DMOG, KKC226 and FG-2216 for 24 h. Results: DMOG (1 mM), KKC226 (0.5 mM) and FG-2216 (30 μM) significantly reduced oxygen consumption after 24 h (32%, 47% and 35%, respectively) and increased HIF-1±mRNA expression in CDCs (215%, 168% and 154%, respectively). However, 24-h treatment with PHIs did not alter the cell proliferation. Further, KKC226 significantly increased c-Kit mRNA expression by 1.5-fold and reduced the cardiac mesenchymal cell marker, CD90 by 0.6-fold. DMOG and FG2216 reduced CD90 by 0.2-fold and 0.3-fold, respectively. EPO mRNA was increased in CDCs treated with KKC226 (2.2-fold) and FG-2216 (2.4-fold) but not in those treated with DMOG, compared with controls. DMOG and KKC226 increased VEGF secretion, 8.8-fold and 2.8-fold, respectively. Of note, PHIs significantly increased glucose uptake and lactate accumulation in the culture medium, compared with controls, suggesting increased glycolytic metabolism. In conclusion, DMOG, KKC226 and FG-2216 stabilised and activated HIF, which induced metabolic changes in the CDCs. This work could impact on novel therapies for myocardial infarction.